2015
DOI: 10.1021/acs.jnatprod.5b00233
|View full text |Cite
|
Sign up to set email alerts
|

Harpagoside Inhibits RANKL-Induced Osteoclastogenesis via Syk-Btk-PLCγ2-Ca2+ Signaling Pathway and Prevents Inflammation-Mediated Bone Loss

Abstract: Harpagoside (HAR) is a natural compound isolated from Harpagophytum procumbens (devil's claw) that is reported to have anti-inflammatory effects; however, these effects have not been investigated in the context of bone development. The current study describes for the first time that HAR inhibits receptor activator of nuclear factor κB ligand (RANKL)-induced osteoclastogenesis in vitro and suppresses inflammation-induced bone loss in a mouse model. HAR also inhibited the formation of osteoclasts from mouse bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 64 publications
2
44
0
Order By: Relevance
“…An imbalance of this process leads to the onset of osteoporosis, a multifactorial age-related disease characterized by increased bone fragility, with a major incidence in women ( Conversely, Chung et al (2016) showed that harpagoside, in addition to the stimulating osteoblast proliferation activity, was also able to restore OVX-induced destruction of trabecular bone. Actually, this contrasting result, compared with the findings of Kim et al (2015), could be related, albeit partially, to significant differences in study design. Indeed, although the oral dose of harpagoside (2-10 mg/kg) was the same in both studies, the duration of treatment, in Chung's paradigm (12 weeks), was much longer compared with Kim's study (4 weeks), thus affecting pharmacological response, in vivo.…”
Section: Osteoporosismentioning
confidence: 63%
See 2 more Smart Citations
“…An imbalance of this process leads to the onset of osteoporosis, a multifactorial age-related disease characterized by increased bone fragility, with a major incidence in women ( Conversely, Chung et al (2016) showed that harpagoside, in addition to the stimulating osteoblast proliferation activity, was also able to restore OVX-induced destruction of trabecular bone. Actually, this contrasting result, compared with the findings of Kim et al (2015), could be related, albeit partially, to significant differences in study design. Indeed, although the oral dose of harpagoside (2-10 mg/kg) was the same in both studies, the duration of treatment, in Chung's paradigm (12 weeks), was much longer compared with Kim's study (4 weeks), thus affecting pharmacological response, in vivo.…”
Section: Osteoporosismentioning
confidence: 63%
“…Intriguingly, experimental studies also suggested the potential application of devil's claw as protective agent in osteoporosis. Chung et al () showed harpagide efficacy in exerting protective activity against bone loss in ovariectomized (OVX) mice, an animal model largely used to reproduce estrogen insufficiency‐related postmenopausal osteoporosis (Kim et al, ). Particularly, harpagide was found effective in stimulating osteoblast and blunting RANKL‐induced osteoclast differentiation.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The RANKL–RANK axis also stimulates the Ca 2+ –NFATc1 signaling pathway by activating PLCγ. During osteoclastogenesis, activated PLCγ hydrolyzes phosphatidylinositol-4,5-biphosphate (PIP2) to inositol-1,4,5-triphosphate (IP3), thereby upregulating both the intracellular Ca 2+ and the NFATc1 activation (Negishi-Koga and Takayanagi, 2009; Hwang and Putney, 2011; Kim et al, 2014, 2015). Oxidative stress stimuli transmitted by increased intracellular production of ROS could play as the secondary messengers in RANKL-induced osteoclast signaling pathways (Lee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…With the aging of the global population, such diseases as rheumatoid arthritis (RA), osteoarthritis, and other bone metabolic disorders are increasingly impacting public health as well as the economy (1,2). Because current treatments for arthritis are inefficient, produce substantial side effects, and tend to be expensive, natural products, which are devoid of such disadvantages, offer novel treatment opportunities (3).…”
Section: Introductionmentioning
confidence: 99%